Induction chemotherapy in pancreatic cancer: CA 19-9 may predict resectability and survival. Issue 2 (February 2020) - Heger, Ulrike; Sun, Huihui; Hinz, Ulf; Klaiber, Ulla; Tanaka, Masayuki; Liu, Bing; Sachsenmaier, Milena; Springfeld, Christoph; Michalski, Christoph W.; Büchler, Markus W.; Hackert, Thilo
Abstract: Background: Preoperative/Neoadjuvant treatment (NT) is increasingly used in unresectable pancreatic cancer (PDAC). However, ∼40% of patients cannot be resected after NT and reliable preoperative response evaluation is currently lacking. We investigated CA 19-9 levels and their dynamics during NT for prediction of resectability and survival. Methods: We screened our institution's database for patients who underwent exploration or resection after NT with gemcitabine-based therapy (GEM) or FOLFIRINOX (FOL). Pre- and post-NT CA 19-9, resection rate and survival were analyzed. Results: Of 318 patients 165 (51.9%) were resected and 153 (48.1%) received exploration. In the FOL group ( n = 103; 32.4%), a post-NT CA 19-9 cutoff at 91.8 U/ml had a sensitivity of 75.0% and a specificity of 76.9% for completing resection with an AUC of 0.783 in the ROC analysis (95% CI: 0.692–0.874; p < 0.001. PPV: 84.2%, NPV: 65.2%). Resected patients above the cutoff did not benefit from resection. Post-NT CA 19-9 <91.8 U/ml (OR 11.63, p < 0.001) and CA 19-9 ratio of <0.4 (OR 5.77, p = 0.001) were independent predictors for resectability in FOL patients. Discussion: CA 19-9 levels after neoadjuvant treatment with FOLFIRINOX predict resectability and survival of PDAC more accurately than dynamic values and should be incorporated into response evaluation and surgical decision-making.